2016
DOI: 10.4240/wjgs.v8.i10.679
|View full text |Cite
|
Sign up to set email alerts
|

Increasing trend in retained rectal foreign bodies

Abstract: AIMTo highlight the rising trend in hospital presentation of foreign bodies retained in the rectum over a 5-year period.METHODSRetrospective review of the cases of retained rectal foreign bodies between 2008 and 2012 was performed. Patients’ clinical data and yearly case presentation with data relating to hospital episodes were collected. Data analysis was by SPSS Inc. Chicago, IL, United States.RESULTSTwenty-five patients presented over a 5-year period with a mean age of 39 (17-62) years and M: F ratio of 2:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 17 publications
0
32
0
6
Order By: Relevance
“…The true incidence in our population is unknown as many cases are unreported due to the nature of the condition [2]. Abraham et al reported that there is an increase in incidence of rectal foreign bodies presented to the emergency departments in the United Kingdom [3]. Patients normally seek medical attention when attempts at self removal fails at home.…”
Section: Introductionmentioning
confidence: 94%
“…The true incidence in our population is unknown as many cases are unreported due to the nature of the condition [2]. Abraham et al reported that there is an increase in incidence of rectal foreign bodies presented to the emergency departments in the United Kingdom [3]. Patients normally seek medical attention when attempts at self removal fails at home.…”
Section: Introductionmentioning
confidence: 94%
“…Fallberichte ziehen sich in der Literatur durch sämtliche Jahrzehnte [2]. Manche Autoren beschreiben gar eine steigende Inzidenz [3,4].…”
Section: Kolorektale Fremdkörpereine Herausforderung Für Patient Und unclassified
“…These are difficult to visualize and remove. 2 Lowlying FBs that are below the recto-sigmoid junction and normally palpable on DRE and easier to visualize and remove. Patients with CRFBs are usually aware of their presence and often present requesting removal.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CRFBs are usually aware of their presence and often present requesting removal. 2 and usually present with rectal pain, per rectal bleeding, constipation and pain in the abdomen. More serious complaints are indicative of perforation causing peritonitis, fever, vomiting, or severe pain etc.…”
Section: Introductionmentioning
confidence: 99%